Ocean circulation and frontal structure near the southern Kerguelen Plateau: The physical context for the Kerguelen Axis ecosystem study. (April 2020) - Bestley, Sophie; van Wijk, Esmee; Rosenberg, Mark; Eriksen, Ruth; Corney, Stuart; Tattersall, Katherine; Rintoul, Stephen
Abstract: Oceanographic observations from ships, floats and remote sensing are used to describe the ocean circulation and frontal structure from the southern Kerguelen Plateau to the Antarctic margin. The flow of the Antarctic Circumpolar Current (ACC) is largely zonal upstream of the Kerguelen Plateau. The southern branch of the Polar Front and the northern branch of the southern ACC front (SACCF) are deflected to the north by the topography and cross the plateau through the Fawn Trough. The southern branch of the SACCF and the southern boundary of the ACC pass to the south of Banzare Bank, through the Princess Elizabeth Trough. These fronts turn sharply to the north on the eastern flank of the plateau, then retroflect to the south before continuing eastward. Satellite altimetry and float trajectories suggest the ACC regime to the east of the plateau is eddy-rich and characterised by extensive meandering of the ACC fronts, in contrast to the low eddy energy and zonal flow observed west of the plateau. The Antarctic Slope Current flows west along the upper continental slope, with hydrographic data indicating some of the flow turns offshore and feeds the Southern Boundary flow in the Western Boundary Current. Flow over the plateau itself is relatively quiescent and floats in this region have a long residence time (> 1 year). The regional circulation is closely associated with the distribution of biological productivity in surface waters, as revealed in satellite measurements of ocean colour, including high productivity in subpolar waters, along the eastern edge of the plateau and over the Antarctic continental shelf, moderate productivity over the plateau, and low productivity in ACC waters in the Fawn Trough and north of the SACCF.